A Fire Regime Zoning System for China - Zong, Xuezheng; Tian, Xiaorui; Liu, Jialei (Frontiers in Forests and Global Change, 2021)
Understanding fire regimes is central to fire management. In our study, we analyzed the fire weather and forest fire regime of China using fire data from satellite remote sensing and statistics from 2000 to 2020. The fire weather index system was calculated from observed weather data for 2007 to 2017. Using qualitative and quantitative methods, we created a zoning system for China based on the spatial distribution characteristics of fire regimes and vegetation. The fire seasons varied between regions because of differences in vegetation, climate and ignition sources. The fire seasons in the north were spring and autumn. In the south and southwest forest regions, the fire seasons were winter and spring. Most forest fires occurred in southern China, but the average burned area per fire was lower compared with fires in the northeast. The zoning system includes 13 forest fire regime zones with specific fire characteristics according to quantitative variables. These zones are further divided into 17 fire regime units based on qualitative variables. Each fire regime unit has unique characteristics for regime, climate and vegetation type. Human activity was the main cause of fires, especially in south China, where the population density is high. Fire management should be tailored to each fire regime type based on fire characteristics and management targets.